Peran Kementerian Agama dalam mempromosikan moderasi beragama di era digital - firmanda taufiq; ayu maulida alkholid (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2021)
Religious moderation is an important key in the religious diversity landscape. This concept is one of the alternatives and solutions amid various conflicts and problems in the name of the division in the name of religion, especially in Indonesia. These problems must be responded to and find solutions so that religious problems in Indonesia can be unraveled. Especially during the digital era like today, promoting and actualizing religious moderation in the context of religion in Indonesia is an absolute must. This study seeks to explore and examine the role of the Ministry of Religion as one of the government institutions that functions as a policymaker in religious activities, especially in the issue of implementing religious moderation in Indonesia, especially in the context of the current digital era. This study uses a descriptive-analytical approach by taking some data and references sourced from several journal articles, books, and the Ministry of Religion website, as well as various kinds of literature that support the topic in the discussion of this research. Researchers found that the Ministry of Religion seeks to encourage religious moderation in its policies and programs, especially in dealing with religious conflicts in Indonesia, especially conflicts between religious believers, strengthening radicalism, and the emergence of transnational religious ideas that have begun to develop and enter Indonesia, as well as spreading understanding in a structured and massive manner. This is done to muffle and reduce the occurrence of various acts and acts of radicalism and extremism in Indonesia. ***Moderasi beragama merupakan kunci penting dalam lanskap keragaman agama. Konsep ini menjadi salah satu alternatif dan solusi di tengah berbagai konflik dan permasalahan yang mengatasnamakan pemecahbelahan atas nama agama, khususnya di Indonesia. Permasalahan-permasalahan tersebut harus direspon dan dicarikan solusi agar permasalahan keagamaan di Indonesia dapat terurai. Apalagi di tengah era digital seperti sekarang ini, menggalakkan dan mengaktualisasikan moderasi beragama dalam konteks beragama di Indonesia menjadi hal yang mutlak. Kajian ini berupaya menelusuri dan mengkaji peran Kementerian Agama sebagai salah satu lembaga pemerintah yang berfungsi sebagai pembuat kebijakan dalam kegiatan keagamaan, terutama dalam persoalan implementasi moderasi beragama di Indonesia, terutama dalam konteks era digital saat ini. Penelitian ini menggunakan metode pendekatan deskriptif-analisis dengan mengambil beberapa data dan referensi yang bersumber dari beberapa artikel jurnal, buku, dan website Kementerian Agama, serta berbagai literatur yang mendukung topik dalam pembahasan penelitian ini. Peneliti menemukan bahwa Kementerian Agama berupaya untuk mendorong moderasi beragama dalam kebijakan dan programnya, terutama dalam menangani konflik agama di Indonesia, khususnya konflik antarumat beragama, menguatnya paham radikalisme, dan munculnya ide-ide keagamaan transnasional yang sudah mulai berkembang dan masuk ke Indonesia, serta menyebarkan pemahamannya secara terstruktur dan masif. Hal ini dilakukan untuk meredam dan mengurangi terjadinya berbagai aksi dan tindakan radikalisme dan ekstremisme di Indonesia.